2009
DOI: 10.1016/j.freeradbiomed.2008.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Lon protease is a human stress protein

Abstract: The targeted removal of damaged proteins by proteolysis is crucial for cell survival. We have shown previously that the Lon protease selectively degrades oxidized mitochondrial proteins, thus preventing their aggregation and cross-linking. We now show that the Lon protease is a stress-responsive protein that is induced by multiple stressors, including heat shock, serum starvation, and oxidative stress. Lon induction, by pre-treatment with low-level stress, protects against oxidative protein damage, diminished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
98
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 51 publications
8
98
1
1
Order By: Relevance
“…Thus, the effects of Lon depletion may be species-or cell type-specific. As in a recent report with human rhabdomyosarcoma cells (39), depletion of Lon protease in Drosophila Schneider cells results in an increase in the levels of oxidized proteins in mitochondria, indicating that Lon is responsible for degradation of oxidized mitochondrial proteins, and suggesting that variations in cell viability as a result of Lon depletion may reflect varying cellular tolerances for oxidative damage to mitochondrial proteins.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, the effects of Lon depletion may be species-or cell type-specific. As in a recent report with human rhabdomyosarcoma cells (39), depletion of Lon protease in Drosophila Schneider cells results in an increase in the levels of oxidized proteins in mitochondria, indicating that Lon is responsible for degradation of oxidized mitochondrial proteins, and suggesting that variations in cell viability as a result of Lon depletion may reflect varying cellular tolerances for oxidative damage to mitochondrial proteins.…”
Section: Discussionsupporting
confidence: 60%
“…Further study revealed that the ROSinduced degradation of UNG1 was not proteasome dependent; rather, LonP1 was responsible for UNG1 degradation under oxidative stress. LonP1 is a mitochondrial ATP-dependent protease [50], which is induced by oxidative stress to degrade oxidized proteins within the mitochondrial matrix [50][51][52][53][54]. Although the molecular mechanisms leading to degradation of UNG1 are still not clear, our study reveals that ROS promotesLonP1-dependent UNG1 degradation whereas the UNG1-PRDX3 interaction protects UNG1 from ROS-mediated degradation.…”
Section: Discussionmentioning
confidence: 66%
“…Specific thioredoxin, TrxR and Grx isoforms localize to mitochondria in mammalian, and presumably avian, cells (see Page et al 2010b). Similarly, mitochondria contain a Lon protease with similar stress-inducible protein degradation functions to the 20S/26S proteasome (Ngo and Davies 2009). These specific mitochondrial activities may be upregulated concomitantly with increased longevity, a possibility that should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%